An active, skeletally anchored transpalatal appliance for derotation, distalization and vertical control of maxillary first molars - Hourfar, Jan; Ludwig, Björn; Kanavakis, Georgios (Journal of orthodontics, 2014)
Objective: The objective of this investigation was to evaluate treatment outcomes of the skeletally anchored ‘Frog’ appliance. Design: A single-centre, retrospective study was performed. Setting: Private orthodontic practice. Participants: Patients who had undergone comprehensive orthodontic treatment with the skeletally anchored ‘Frog’ appliance. Methods: 43 participants (20 males and 23 females) who had received treatment with the skeletally anchored ‘Frog’ appliance where included. In order to explore dentoalveolar and skeletal treatment outcomes, pre- (T1) and post- (T2) treatment measurements were performed on patients’ plaster models and cephalometric images. Comparisons between T1 and T2 were made by means of a Student’s t-test. All statistical analyses were conducted at the 0·05 level of statistical significance. Results: Study model analysis revealed a statistically significant derotation of maxillary molars (μΔT2−T1 = 9·5°, P<0·001) as well as an increase in transverse arch dimensions at the end of treatment (μΔT2-T1 = 2·2 mm, P<0·001). Cephalometric changes included bodily distalization of maxillary molars (μΔ(T2-T1) = −1·9 mm, P<0·001), as well as noticeable angular displacement (μΔT2-T1 = 4·1°, P = 0·004). No significant anchorage loss was observed, as displayed by the limited change in maxillary incisor position (μΔ(T1-T2) = 0·2 mm, P = 0·45). In addition, excellent vertical control of the maxillary molars was achieved, with no change in the mandibular plane (ML/NSL) angle (μΔT2-T1 = 0·3°, P = 0·38). Conclusions: The skeletal ‘Frog’ is effective in derotating and distalizing maxillary molars without anchorage loss and with excellent vertical control.
Gesehen am 16.02.2021